ToF-SIMS sputter depth profiling of interphases and coatings on lithium metal surfaces - Maximilian Mense; Marlena M. Bela; Sebastian P. Kühn; Isidora Cekic-Laskovic; Markus Börner; Simon Wiemers-Meyer; Martin Winter; Sascha Nowak (Communications Chemistry)
Abstract Lithium metal as a negative electrode material offers ten times the specific capacity of graphitic electrodes, but its rechargeable operation poses challenges like excessive and continuous interphase formation, high surface area lithium deposits and safety issues. Improving the lithium | electrolyte interface and interphase requires powerful surface analysis techniques, such as ToF-SIMS sputter depth profiling.This study investigates lithium metal sections with an SEI layer by ToF-SIMS using different sputter ions. An optimal sputter ion is chosen based on the measured ToF-SIMS sputter depth profiles and SEM analysis of the surface damage. Further, this method is adapted to lithium metal foil with an intermetallic coating. ToF-SIMS sputter depth profiles in both polarities provide comprehensive insights into the coating structure. Both investigations highlight the value of ToF-SIMS sputter depth profiling in lithium metal battery research and offer guidance for future studies.